The treasury bill market in the Bahamas: an efficiency analysis - Seymour, Josephine ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Analyzes the efficiency of the market and indicates trends and developments which could assist in enhancing the volume of information available for policy makers.